Landuse Change Analysis in Relation to Hydrological Characteristic of Krueng Aceh Watershed - . NASRULLAH; B. KARTIWA (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2010)
Landuse change at watershed area tend to increase its intensity according to space and time, as logical consequence of development activity and high resident growth rate. The increase of this intensity can bring negetive influence to hydrological conditions i.e: the increasing of peak discharge, discharge fluctuation between dry and wet season, run off coefficient andalso drought and flooding. Remote sensing, technology based on time and series of spatial satelite image, is the best methodology for observing landuse change. This method is more accurate, faster and cheaper than classic method through aerial photograph analysis. The aims of this research are to identify and characterize watershed outlet, to evaluate land cover change and to establish the discharge model as function of land cover change scenarios. This research was conducted from January to December 2005 at Krueng Aceh watershed, Nangroe Aceh Darussalam Province. This activity was covered identification and characterization of watershed outlet, including determination of the AWLR installation point, measurement of river cross section, and also measurement of waterflow velocity. Other activities are image satelite and landuse change analysis. Meanwhile dailydischarge simulation was conducted using a model base on GIS that correlated with land cover change scenarios. Discharge simulation according to scenario 3 (forest is decreasing 50%, mixed garden and bare soil are decreasing 25%, paddy field and settlement is increasing 400%) shows that rainfall event about 29.4 mm on July 31, 2002 and 64 mm on October 29, 2002 stimulate peak discharge of 66.3 and 161.9 m3 s-1, or increasing 21.6 an